HISTORY OF MINING WORKS OF KHANATE OF KOKAN (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
this article is devoted to the history of mining in the territory of the Kokan Khanate, including the state of mining in the beginning of the 18th - 19th centuries, the development of mining, the mines operated by Kaoliyat and their historical locations, traditions and methods of mining. analyzed on the basis of extensive historical sources and scientific literature. The article provides information about the oil turquoise, emerald, gold, lead, copper, mercury, silver, spirit, and crystal deposits of the Kokan Khanate.